The influence of growth regulators on the ripening period, yield and quality of melon of the medium-ripened variety Osen - N. B. Ryabchikova; M. S. Kornilova (Овощи России, 2022)
This article shows the influence of growth regulators and methods of their application on the passage of the main interphase periods and growth processes during melon cultivation. The use of growth regulators is one of the promising directions in the cultivation of melons. In the acutely arid areas of the Volgograd Volga region, the use of mineral fertilizers for melon crops, in bagar conditions, was not effective, since there was an acute shortage of moisture in the soil. Therefore, the most effective and promising for creating favorable conditions for the growth and development of melon plants, with the possibility of leveling negative environmental factors, is the use of foliar treatments in the cultivation technology with growth regulators. The studied drugs of the new generation have a wide range of physiological activity. They are designed to influence the parameters of growth and development of plants as a whole in various phases, as well as their organs, as well as the parameters of plant response to environmental factors.Results. Studies have revealed the dependence of the growth processes of melon plants on the methods of using growth regulators, the length of the lashes in the variants of using growth regulators for processing plants during vegetation is longer compared to soaking seeds, with their maximum length in the Phytozont variant (plant treatment) is 12.7-51.3% longer compared to other studied preparations.